2021
DOI: 10.1186/s40729-021-00371-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical implementation of optional implant treatment into pregraduate dental education—mini implants for retention and support of mandibular overdentures

Abstract: Background The primary aim of the study was to evaluate mini implant (MDI) survival, prosthodontic maintenance, and patient-reported outcome measures after conducting an optional pregraduate academic course on patients with mandibular edentulism including fabrication of overdentures and MDI planning and placement as well as chair-side incorporation of the respective restauration. In a prospective clinical study, 20 patients received 80 MDIs that were restored with mandibular overdentures. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In their study, undergraduate dental students placed 40 mini‐implants in 20 patients and restored them with mandibular overdentures. With a total survival rate of 96.25% after a follow‐up of 1 year, the results were in accordance with those reported by postgraduate dentists 32 …”
Section: Discussionsupporting
confidence: 90%
“…In their study, undergraduate dental students placed 40 mini‐implants in 20 patients and restored them with mandibular overdentures. With a total survival rate of 96.25% after a follow‐up of 1 year, the results were in accordance with those reported by postgraduate dentists 32 …”
Section: Discussionsupporting
confidence: 90%
“…Clinical and laboratory studies concerning the retention of total prostheses have examined the placement of endosseous implants to ensure retention for patients with total prostheses [11][12][13]. Other studies have examined non-surgical methods, such as the use of denture adhesives (DAs) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kämmerer et al showed that mini-implants could also achieve satisfactory results. The strict reduction of insertion torque and the best possible preparation of the bone were described as particularly relevant [ 48 ]. Some studies attribute a lower survival rate to wide-diameter implants.…”
Section: Resultsmentioning
confidence: 99%